Oil Prices and the Macroeconomy - Bachmeier, Lance J.; Plante, Michael (My University, 2018)
The combination of high inflation and high unemployment experienced in the 1970s and early 1980s has been perhaps the most important macroeconomic event since the Great Depression. Figure 1 shows that there were two spikes in the price of oil in this time period, and both were followed by large increases in inflation and unemployment. This was widely viewed as evidence that changes in the price of oil have large effects on the economy. Not surprisingly, this episode has been the subject of considerable research.
Citation: Bachmeier, L. and Plante, M. (2018) Oil Prices and the Macroeconomy. Unpublished manuscript.